UPDATE ON HUMAN FASCIOLIASIS IN PERU: DIAGNOSIS, TREATMENT AND CLINICAL CLASSIFICATION PROPOSAL - Marcos, Luis A. (2007)
Human Fasciola hepatica infection in Peru is an emerging infectious disease. In this review we describe the fascioliasis situation in Peru, based on the most recent studies about epidemiology, diagnostic tools and treatment. We propose a new clinical classification according to the stage of the disease. Recent reports have highlighted the clinical variability ranging from an indolent to a severe life-threatening infection. Increasing numbers of human cases have been reported worldwide, especially from the Andean Region in South America. Most common clinical manifestations in the acute phase are: hepatomegaly, fever, weight loss, and eosinophilia. In the chronic phase, it can be mild and unspecific, including: biliary obstruction, bacterobilia, liver cystic calcifications, gallstones, and liver fibrosis. The Rapid Sedimentation Technique described by Lumbreras should be applied to diagnose the chronic phase as well as for epidemiological studies in endemic areas. The direct smear only detects 2% of cases. The novel diagnostic test Fas2 (cathepsin L1) ELISA has a sensitivity of 92.4% and specificity of 83.6% in 634 Peruvian subjects in endemic areas and it is helpful for both the acute and chronic phases. The most common radiological abnormalities in the acute phase are: track-like hypodense hepatic lesions, liver “abscesses” and/or subcapsular hematomas. Abdominal ultrasound has a low sensitivity in chronic cases and is not recommended for screening. Triclabendazole is the treatment of choice even with a single dose (cure rate ≥ 90 %) for both phases, but resistance is now a concern in animals. The new arsenal of available information can be applied to preventionand control programs in Peru.